PIETY ON CONTESTATION - Muhammad Ansor; Yaser Amri; Ismail Fahami Arrauf (Al Qalam, 2014)
This article studied the phenomenon of contestation between orang Sunnah and orang Yasin in Sidodadi, Aceh Tamiang, to gain the recognition of being the most pious Muslim adherent. The research zoomed in on exploring the shape of the contestation and the socio-religious changes that may occur due to the existence of the mentioned contest. The researchers interviewed a dozens of informant, observed their religious practices and the strategy that they launch to propagate their belief and recruit new members. The study showed that the contestation between the two community take place in almost all religious practices. Some of the worth mentions are ritual practices, broadening and enhancing the religiosity of respective community members, or the approach they used in approaching Islam. Apart from that, the contestation between these two groups also triggered the negotiation and reconciliation of Islamic practices of both groups. The reconciliation of religious practice is in accordance with the "culture in between " theory as proposed by Homi K Bhabha in which he believes that truly there are always no clear boundaries between two groups of different credentials. In Sidodadi, the credentials difference of each group to actualize the ideal of Islam in managing the house of God for instance, triggers the struggle of both groups for the control of the mosques and mushollas in one hand, and in other hand it brings out the empathy of each community to revive the religious activities in worship places, though adapted with the credential feature of their respective groups. Keywords: Piety, Orang Sunnah, Orang Yasin, Aceh Tamiang